Retroperitoneal Liposarcoma: A Comprehensive Review. (April 2015) - Vijay, Adarsh; Ram, Lakshmi
Abstract : Retroperitoneal liposarcomas are rare mesenchymal tumors of the retroperitoneum that typically present with advanced disease and often carry a poor prognosis. Because of their rarity and anatomic location, these malignant tumors can cause a diagnostic dilemma and present several therapeutic challenges. They are usually associated with a high rate of recurrence despite grossly complete resection, thus requiring long-term and often indefinite follow-up. Relevant data on this topic was procured and synthesized with the aid of a comprehensive Medline search in addition to oncologic, pathologic, urologic, radiologic, and surgical literature review on retroperitoneal sarcomas. This article provides an in-depth review into the natural history, pathology, clinical manifestations, and prognostic features of retroperitoneal liposarcomas. It also discusses the reliability of diagnostic procedures and novel curative approaches that are currently being evaluated for the disease.